Silver Recovery from X-ray Film Waste by Leaching and Precipitation Method Using Sodium Hydroxide and Sodium Sulfide - Soja Siti Fatimah; Wiwi Siswaningsih; Ali Kusrijadi; Fikri Aziz Shalahuddin (Syarif Hidayatullah State Islamic University, 2020)
Silver recovery research from x-ray film waste by leaching and precipitation method using NaOH and Na2S aims to determine the optimum conditions in silver recovery. The parameters optimated in this study were the concentration of the precipitants, leaching temperature and the effect of the type of precipitants on the precipitated time. The results showed that the NaOH and Na2S precipitants were able to recover silver optimally at a concentration of 1.5 M. The optimum leaching temperature of the film with the Na2S precipitant to recover silver was at 25oC, whereas in the NaOH precipitant the film leaching temperature only affected the time of precipitation. Therefore, the formation of precipitate using Na2S is more efficient than NaOH, but the acquisition of silver is better to use NaOH than Na2S.